Foucault's Queer Virgins: An Unfinished History in Fragments. - HUFFER, LYNNE (Foucault Studies, 2021)
This essay attends to the place of virginity at the center of the fourth volume of Michel Foucault's History of Sexuality, Confessions of the Flesh. Reading virginity through a rhetorical lens, the essay argues for an ethics and a politics of counter-conduct in Foucault characterized by chiasmus, a rhetorical structure of inverted parallelism. That chiastic structure frames Foucault's Confessions, and all of his work, as a fragmented, self-hollowing speech haunted by death and the dissolution of the subject. The essay reads Foucault as apophatic speech that returns to us, no longer itself, made strange. In that deathly movement of eternal recurrence, Foucault's Confessions speak after death from the x'd out place of the queer virgin: on a threshold that separates life from death, in a movement of metanoia or ethical conversion. As an unfinished history in fragments, the essay's form brings attention to incompletion as a crucial aspect of Foucault's work. The fragmentation that characterizes an unfinished history underscores poetic discontinuity as the hallmark of Foucault's genealogical method and thought.